2020
DOI: 10.1002/adem.202000325
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical Properties of Robocasted Barium Titanate Ceramics

Abstract: This work presents the fabrication of dense polycrystalline barium titanate (BaTiO3, BT) for electromechanical transduction using robocasting and cold isostatic pressing (CIP). The use of CIP as post‐treatment is proposed to eliminate defects and increase the density of robocasted parts to improve the piezoelectric performance. For robocasting, pastes containing 50 and 52 vol% are developed; the resulting green robocasted parts are CIPed at 100 and 150 MPa. Using this proposed technique, samples robocasted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…For bone substitutes, the d 33 value is relevant and can be directly compared with the value of the bone . For sensing or energy harvesting applications, however, FOM 33 is the relevant parameter. , This quantity directly depends on the d 33 value and the relative permittivity (see eq ). The higher the d 33 and the lower the relative permittivity, the higher values are achieved for the FOM 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For bone substitutes, the d 33 value is relevant and can be directly compared with the value of the bone . For sensing or energy harvesting applications, however, FOM 33 is the relevant parameter. , This quantity directly depends on the d 33 value and the relative permittivity (see eq ). The higher the d 33 and the lower the relative permittivity, the higher values are achieved for the FOM 33 .…”
Section: Resultsmentioning
confidence: 99%
“…A broad overview of additive-manufactured piezoelectric ceramics is given by Chen et al According to this review, BT and BT-based ceramics have already been investigated using AM techniques such as stereolithography, binder jetting, , extrusion-free forming, fused deposition modeling, , selective laser sintering, electrical poling-assisted additive manufacturing, or solvent evaporation-assisted 3D printing . Only a few studies deal with the extrusion or DIW of BT, and only a small fraction of those investigate the production of 3D-printed ceramic bodies. , …”
Section: Introductionmentioning
confidence: 99%
“…As such, the temperature‐dependent voltage coefficient has been calculated for the KNN samples, as shown in Figure 8. The room‐temperature g 33 was found to be 28 × 10 −3 Vm/N, which is significantly higher than lead‐free compositions such as BaTiO 3 and comparable to that of lead‐based soft PZT compositions 38,39 . However, it should be mentioned here that only high g 33 value do not ensure optimized energy harvesting parameters, that is, the transduction coefficient.…”
Section: Resultsmentioning
confidence: 86%
“…The room-temperature 𝑔 33 was found to be 28 × 10 −3 Vm/N, which is significantly higher than lead-free compositions such as BaTiO 3 and comparable to that of lead-based soft PZT compositions. 38,39 However, it should be mentioned here that only high 𝑔 33 value do not ensure optimized energy harvesting parameters, that is, the transduction coefficient. As such, despite the comparable 𝑔 33 of KNN with that of soft PZT, the transduction coefficient is lower for KNN due to the relatively low d 33 value.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of large anisotropic particles on paste rheology led to a drastic decrease of G 0 due to the relative size of the platelets compared to the equiaxed matrix particles, while the slight increase of σ y can be linked to the alignment of platelets during shearing. In a similar work, Lorenz et al [86] showed the influence of BaTiO 3 content on the overall paste rheological properties. The powder had a bimodal distribution with comparatively small size of d 50 ¼ 1.2 μm.…”
Section: Influence Of Particle Features and Solid Loading On Ink Rheo...mentioning
confidence: 89%